Expectations and experiences of temporarily studying abroad - Per A. Nilsson (História - Revista da Faculdade de Letras da Universidade do Porto, 2013)
This tentative study focuses on the experiences of outbound exchange students and underlines the international relations component among contemporary universities. The aim is to investigate to what extent the expectations of outbound exchange students are being met in a population of students who had temporarily studied abroad. In this study, Umeå University, Sweden, is used as a case. The study was inspired by Plog’s studies (1974, 2001) in the field of tourism and hospitality research. Exchange students show similarities with tourists when it comes to choosing study destinations. This study partially confirms Plog’s model. Students who are outgoing and self-confident seem to choose non-English speaking countries. In addition, this study highlights what incentives students have, to become exchange students and most importantly how they value this experience. The respondents had positive expectations before departing as exchange students and they returned with even more positive attitudes.